Fermentation studies of stored cocoa beans - Abdul Samah, O.; Ibrahim, N.; Alimon, H.; Abdul Karim, M.I. (Kluwer Academic Publishers, 1993)
Acetic and lactic acid bacteria on fermented cocoa beans were maximally 2.0×106 and 1.9×106 c.f.u./g wet wt, respectively. Acetic and lactic acids were detected on the second and fourth days of fermentation and were maximally 140 and 45 mg/10 g beans, respectively. There was a positive correlation between the sizes of the relevant microbial populations and the amounts of acids produced during fermentation.